2005
DOI: 10.1596/1813-9450-3477
|View full text |Cite
|
Sign up to set email alerts
|

Agglomeration, Transport, and Regional Development in Indonesia

Abstract: How effective are public interventions in addressing significant regional disparities in formal manufacturing concentration in a developing economy? We examine the aggregate and sectoral geographic concentration of manufacturing industries for Indonesia, and estimate the impact of factors influencing location choice at the firm level. We distinguish between natural advantage, including infrastructure endowments, wage rates, and natural resource endowments, and production externalities, arising from the co-loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 37 publications
0
38
0
Order By: Relevance
“…Examples for developing countries include Deichman, Fay, Koo and Lall (2002) for Southern Mexico, Lall, Funderburg and Yepes (2004) for Brazil, Lall, Shalizi and Deichman (2004) for India, and Deichmann, Kaiser, Lall and Shalizi (2005) for Indonesia. All these studies find that accessibility is a major determinant of firm productivity.…”
Section: Models Explicitly Including Spatial Variablesmentioning
confidence: 99%
“…Examples for developing countries include Deichman, Fay, Koo and Lall (2002) for Southern Mexico, Lall, Funderburg and Yepes (2004) for Brazil, Lall, Shalizi and Deichman (2004) for India, and Deichmann, Kaiser, Lall and Shalizi (2005) for Indonesia. All these studies find that accessibility is a major determinant of firm productivity.…”
Section: Models Explicitly Including Spatial Variablesmentioning
confidence: 99%
“…Road availability is a significant determinant of investment in Hungary (Boudier‐Bensebaa 2005). The presence of good port facilities is also essential for foreign investors (Belderbos and Carree 2002; Deichmann et al . 2005).…”
Section: Introductionmentioning
confidence: 99%
“…What remains to be done is to relate these results to the issues of principle that previous research brought to light. Returning to NEG theories, the relationship between decreasing transport costs and a subsequent concentration of activities to major cities, often located at a far distance, generate an increased demand for longdistance mobility among rural people (Krugman 1996;Deichmann et al 2005Deichmann et al , 2008Deichmann et al , 2009. This is especially the case in situations where the transport system is centred on a primate city (Krugman 1996).…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Empirical studies using a NEG perspective (such as Deichmann et al 2005Deichmann et al , 2008Deichmann et al , 2009) have shown how proximity and distance to large urban areas, as well as resource endowments and production externalities influence concentration (proximity benefits knowledge transfers and a larger specialized labour supply). As NEG places cities at the centre and predicts patterns of specialization as the distance from cities increases, a systematic relationship between distance from urban centres and types of activities is expected to be found over geographical space.…”
Section: Driving Forces Of Rural-urban Spatial Interactionmentioning
confidence: 99%